2018
DOI: 10.1111/resp.13441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPAP on airway reactivity and airway inflammation in children with moderate–severe asthma

Abstract: Background and objective: Asthma is characterized by airway hyperreactivity and airway inflammation. We previously demonstrated that adults with mild well-controlled asthma exhibited a marked decrease in airway reactivity (PC20 increased >2-fold) after using nocturnal continuous positive airway pressure (CPAP) for 1 week. If CPAP produces a similar suppression of airway reactivity in children with moderate–severe asthma, who require chronic use of corticosteroids, then this non-pharmacological therapy might pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Similarly, in adults with stable asthma, results showed that nighttime CPAP use for 7 days reduced airway reactivity [13]. Conversely, the use of nighttime CPAP (8-10 cmH 2 O) for 4 weeks in children and adolescents with moderate-to-severe asthma did not reduce airway reactivity in a methacholine-induced bronchoconstriction test [29]. Factors such as disease severity, age, time, and period of CPAP use may have been decisive for a lack of consensus on the effects of CPAP on physical performance.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in adults with stable asthma, results showed that nighttime CPAP use for 7 days reduced airway reactivity [13]. Conversely, the use of nighttime CPAP (8-10 cmH 2 O) for 4 weeks in children and adolescents with moderate-to-severe asthma did not reduce airway reactivity in a methacholine-induced bronchoconstriction test [29]. Factors such as disease severity, age, time, and period of CPAP use may have been decisive for a lack of consensus on the effects of CPAP on physical performance.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the results of the study by Holbrook et al . in 2016, the current study by Praca et al . is likely underpowered to show an effect of CPAP if one truly exists.…”
mentioning
confidence: 86%
“…Extending the same line of research to paediatric asthma, in a recent publication in Respirology , Praca et al . present the findings of a small RCT of CPAP versus sham therapy for moderate to severe asthma in children aged 8–17 years . The authors used a 1‐month trial of CPAP at a pressure of 8–10 cm H 2 O compared to sham CPAP of 2 cm H 2 O and defined adherence using the typical cut‐off from adult studies of obstructive sleep apnoea (OSA) treatment of >4 h for >70% of nights.…”
mentioning
confidence: 99%